1990
DOI: 10.1080/00221325.1990.9914641
|View full text |Cite
|
Sign up to set email alerts
|

Mothers' Use of Personal Pronouns when Talking with Toddlers

Abstract: The verbal interaction of 2-year-old children (N = 46; 16 girls, 30 boys) and their mothers was audiotaped, transcribed, and analyzed for the use of personal pronouns, the total number of utterances, the child's mean length of utterance, and the mother's responsiveness to her child's utterances. Mothers' use of the personal pronoun we was significantly related to their children's performance on the Stanford-Binet at age 5 and the Wechsler Intelligence Scale for Children at age 8. Mothers' use of we in social--… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…A meta-analysis helps to resolve discrepancies and yields a more precise estimate of the association between these constructs, that can in turn inform research and practice. 20 and 24 months and is minimal thereafter (Huttenlocher, Haight, Bryk, Seltzer, & Lyons, 1991;Laks et al, 1990). Leaper and Smith (2004) found that girls were slightly more talkative than boys, but the overall effect size was negligible and was significant only in the youngest group of included children (12-35 months).…”
Section: Parental Linguistic Input: Concept Definition and Empirical mentioning
confidence: 99%
See 2 more Smart Citations
“…A meta-analysis helps to resolve discrepancies and yields a more precise estimate of the association between these constructs, that can in turn inform research and practice. 20 and 24 months and is minimal thereafter (Huttenlocher, Haight, Bryk, Seltzer, & Lyons, 1991;Laks et al, 1990). Leaper and Smith (2004) found that girls were slightly more talkative than boys, but the overall effect size was negligible and was significant only in the youngest group of included children (12-35 months).…”
Section: Parental Linguistic Input: Concept Definition and Empirical mentioning
confidence: 99%
“…Language input is typically described in terms of both its quantity and quality. Quantity of input is more consistently defined, and can be operationalized in terms of the number of words or tokens (Rowe, 2012) or number of utterances (Laks, Beckwith, Cohen, & Cohen, 1990) spoken to the child. In contrast, quality of input can refer to a number of different facets of language.…”
Section: Parental Linguistic Input: Concept Definition and Empirical mentioning
confidence: 99%
See 1 more Smart Citation